Synthesis and bioactivity evaluation of some novel sulfonamide derivatives. (3rd July 2017) - Subramanyam, Ch.; Nayab Rasool, Sk.; Janakiramudu, D. B.; Rasheed, S.; Uday Sankar, A.; Naga Raju, C.
GRAPHICAL ABSTRACT: ABSTRACT: A simple and convenient method for the synthesis of biologically active sulfonamide derivatives was achieved. All the title compounds were characterized by spectral and elemental analysis. They were further screened in vitro for their abilities towards antibacterial, antifungal and antioxidant activities. The compound N, N' -(3, 3′-dimethoxybiphenyl-4, 4′-diyl)bis(4-fluorobenzenesulfonamide) (5b ) and N -(3-(9H-carbazol-4-yloxy)-2-hydroxypropyl)-4-fluoro-N-isopropylbenzenesulfonamide (5e ) exhibited good activity when compared to the standard bactericide, Chloramphenicol and fungicide, Ketoconazole respectively. The compounds (2S)- N -((2S, 4S)-5-(4-Chloro-phenylsulfonamido)-4-hydroxy-1, 6-diphenylhexan-2-yl)-3-methyl-2-(2-oxotetrahydropyrim-idin-1(2H)-yl)butan-amide (4f ) and (2S)- N -((2S, 4S)-5-(4-fluorophenylsulfonamido)-4-hydroxy-1, 6-diphenyl-hexan-2-yl)-3-methyl-2-(2-oxotetrahydropyrimidin-1(2H)-yl)bu-tana-mide (5f ) exhibited good antioxidant activity when compared with standard antioxidant, Ascorbic acid.